Gap-free load balancing algorithms in wireless LANs using cell breathing technique - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2014)
A balanced network generally has a fair user distribution among the access points (APs) and enables a maximized overall network throughput. However, there are some hot-spot areas resulting in uneven load distribution among APs. Existing load balancing techniques mostly require hardware or software contribution at user side to control the association of users with APs. Power adjustment techniques at AP side require no modification at user devices, but, coverage reduction can create unserviced areas. We provide a dynamic min-max load balancing algorithm based on power adjustment technique which provides service availability guarantee by dynamically checking the coverage holes. We enhanced the algorithm by increasing awareness to heterogeneous nature of user distribution. We show the effectiveness of the provided algorithms via extensive set of simulations. Simulation results show that the algorithms improved the load balancing among the hot-spot areas up to 10%. © 2014 IEEE.